The Kinetics of the Humoral and Interferon-Gamma Immune Responses to Experimental Mycobacterium bovis Infection in the White Rhinoceros (Ceratotherium simum) - Parsons, Sven D. C.; Morar-Leather, Darshana; Buss, Peter; Hofmeyr, Jennifer; McFadyen, Ross; Rutten, Victor P. M. G.; van Helden, Paul D.; Miller, Michele A.; Michel, Anita Luise (Frontiers in Immunology, 2017)
Mycobacterium bovis is the cause of tuberculosis (TB) in a wide range of species, including white rhinoceroses (Ceratotherium simum). Control of the disease relies on the indirect detection of infection by measuring pathogen-specific responses of the host. These are poorly described in the white rhinoceros and this study aimed to characterize the kinetics of immune responses to M. bovis infection in this species. Three white rhinoceroses were infected with M. bovis and their immune sensitization to this pathogen was measured monthly for 20 months. Cell-mediated immunity was characterized in whole blood samples as the differential release of interferon-gamma in response to bovine purified protein derivative (PPDb) and avian PPD (PPDa) as well as the release of this cytokine in response to the M. bovis proteins ESAT-6/CFP-10. Humoral immunity was quantified as the occurrence or the magnitude of antibody responses to the proteins ESAT-6/CFP-10, MPB83, MPB83/MPB70 and PPDb. The magnitude and duration of immune reactivity varied between individuals; however, peak responses to these antigens were detected in all animals circa 5 to 9 months post infection. Hereafter, they gradually declined to low or undetectable levels. This pattern was associated with limited TB-like pathology at post mortem examination and appeared to reflect the control of M. bovis infection following the development of the adaptive immune response. Measurement of these markers could prove useful for assessing the disease status or treatment of naturally infected animals. Moreover, immune responses identified in this study might be used to detect infection; however further studies are required to confirm their diagnostic utility.